Digital professional learning: triggers in an online badge-driven process - Sanna Brauer; Sanna Ruhalahti; Ville Hallikainen (University of Aberdeen, School of Education, 2018)
Digital open badges describe in detail the expertise and professional competencies achieved in digital environments. "Learning Online" is a Finnish national professional development programme (PDP) of digital pedagogical competencies for vocational teachers. This study aims to identify the students who are particularly motivated by digital open badge-driven learning. The research question asks what triggers learning in such a badge-driven process. The data were collected in 2017 from in-service trained professional teachers and pre-service students (n = 329) of vocational teacher education who have earned digital open badges in a Learning Online PDP. A questionnaire was used to collect data, and a constrained correspondence analysis was conducted to analyse the data. The theoretical approach focuses on the concepts of gamification, the triggers of online learning and the triggering effect of gamification in learning. The study is based on recognized variables affecting motivation in badge-driven learning: progressive challenges and the extent of required performance, enthusiasm for the badge-driven learning, study progress, inspiring gamification, option to study regardless of time and place and optional study paths. The results indicate differences and similarities in the experiences associated with achieved skillset levels. The findings also suggest applying gamification and digital badging for the professional development of both pre- and in-service teachers; gamification motivates students, especially in the beginning of their studies. Furthermore, the results propose considering flexible study options that include customising studies and learning new and upto-date competencies triggering digital open badge-driven learning.